To investigate how disruptive interruptions are on paediatric dispensary accuracy checkers. Issue 2 (12th March 2012) - Sinclair, A.; Terry, D.; Slimm, M.
Abstract : Background: It is well documented that interruptions adversely affect task performance. What is less well known is the impact of interruptions in the context of the paediatric dispensary accuracy checking process. Purpose: To measure the effect that interruptions have on dispensary accuracy checkers. Materials and methods: The study instrument was non-participant, direct observation of a discrete, clearly identifiable step within the dispensing process (the accuracy-checking phase of the dispensing process). A prescription requiring two bottles of medicines to be dispensed was created. The medicines were labelled and placed in a tray together with the required paperwork, additional spoons or oral syringes and a dispensing bag. The operatives, both pharmacists and pharmacy technicians, volunteered to participate and were told that they would be timed accuracy checking a prescription and that the object of the observations was to measure the effect of the environment on their work only and that they themselves were not being assessed. They were also advised that the prescriptions were non-complex, had been clinically screened, and did not contain any errors by design. Each observation (n=34) consisted of two arms as determined by a Latin square. The observations were undertaken in the dispensary and in an office; the latter ensured a quiet environment. In addition a designed interruption was introduced into some of the variants. Results: A statistical analysis of variables was carried out using Minitab. A calculation of least squared means for time showed that individuals were 28.41% less efficient when interrupted in the dispensary. The mean time taken to accuracy check the standard prescription increased from 121.20 s to 155.63. Conclusions: It was found that interruptions adversely affected dispensary accuracy checkers who were checking a standardised prescription of two items in the dispensary at BCH. Dispensary design should support the reduction of interruptions in critical areas.